CSF ADA Determination in Early Diagnosis of Tuberculous Meningitis in HIV-Infected Patients. (6th April 2016) - Ghosh, Gopal Chandra; Sharma, Brijesh; Gupta, B. B.
Abstract : Tuberculous and Cryptococcal meningitis are common in HIV patients. A highly specific and sensitive rapid test for diagnosis of Tuberculous meningitis especially in setting of HIV is not available in developing countries where the burden of disease is high. We measured ADA (adenosine deaminase) levels using spectrophotometric method in the CSF of HIV patients with meningitis to differentiate Tuberculous meningitis from meningitis due to other causes. Kruskal-Wallis test was used to compare ADA values between tuberculous meningitis (TBM) and nontuberculous (non-TB) meningitis patients and a receiver-operating characteristic (ROC) analysis curve was drawn from these values. Levels of ADA in the CSF of patients with TBM were significantly higher than those in patients with meningitis due to other causes. CSF ADA level determination with a cut-off value of 6 IU/L was found to be highly specific and fairly sensitive test for the diagnosis of TBM in HIV positive patients.